Evaluation of Protein, Lactose Content, Boiling Test, Total Solids, and Solid Non-Fat in PFH Cow’s Milk at Moosa Edufarm, West Sumatra - Sujilianto, Silviana; Fridarti; Mulyani, Sri (Andalasian Livestock, 2026)
This study aimed to evaluate the quality of milk produced by Peranakan Friesian Holstein (PFH) cows at Moosa Edufarm, Solok Regency, West Sumatra. Six fresh milk samples from cows at different lactation stages were analyzed for the boiling test (protein stability), total solids (TS), solid nonfat (SNF), protein content, and lactose content. TS and SNF were measured using the gravimetric method, while protein and lactose were analyzed using a Lactoscan device. The results indicated that all milk samples were negative for coagulation in the boiling test, indicating casein stability and freshness. The average TS content was 18.95 ± 4.37% and SNF was 14.45 ± 3.76%, both exceeding the minimum standards set by the Indonesian National Standard (SNI 3141.1-2011). The average protein content was 2.84 ± 0.14%, with the SNI minimum standard of 2.8%. The average lactose content was 4.25 ± 0.21%, within the normal range according to the literature. Variation in results among samples was influenced by feeding regime, lactation stage, cow health, age and post-milking handling. Overall, the milk produced met national quality standards and was suitable for direct consumption and processing into dairy products.